Evaluation of consumer's knowledge, attitude, practice towards herbal tea consumption, preparation and their association with demographic profile - Hussain, Norhayati; Salim, Aida Athirah; Mohamad, Siti Fatimah; Munawar, Nursabrina (Medcrave Group, 2023)
Consumer herbal drinks consumption should be monitored since limited knowledge of possible herbal drinks harmful effects may put the consumer in danger. It is necessary to assess whether the demographic profile shifts the awareness and practice of consumers towards the consumption of herbal tea. This study compares the relationship between demographic profile with knowledge, attitude, and practices of herbal tea. Next, the association between demographic profile with knowledge, attitude and practices of herbal tea was studied. A cross sectional study was conducted using survey questionnaire, distributed using online platform and validated with reliability of Cronbach alpha with value >0.7. Data were analyzed using descriptive statistic, t-test, one-way ANOVA and chi square test. Result showed that from a total of 168 respondents, majority (72.6%) respondents have a moderate knowledge toward herbal tea and about 44.6% respondents have moderate attitude level toward herbal tea. Knowledge and attitude level relationship was insignificant (p>0.05). Moreover, comparison between knowledge level and higher educational level show significant difference (p<0.05) while the association between attitude level with age, occupation, ethnic and highest educational level show significance different at 0.043, 0.003, 0.023 and 0.020 respectively. The significance different shows that, there is measurable different between two group. Consumer consumption practices also varies among the demographic as examples: consumers prefer herbal tea in tea bag compared with other form and consumer with age range 18-26 years old prefer to buy herbal products from hypermarket/minimarket while older consumers prefer to buy from agent/ stockist. The Malaysian consumers are relatively knowledgeable on herbal tea products and believe that herbal teas were safe for consumption. The consumption practices association is used to determine consumer behavior toward herbal tea consumption and their buying decision.